Factors associated with physical inactivity among community dwelling adults in Umuahia, Nigeria : Physical inactivity among community dwelling adults - Patricia Ukegbu; Beulah Ukegbu; Precious Uche; Andrew Ukegbu (Indonesian Nutrition Association, 2022)
Background: Considerable evidence suggests that physical inactivity contributes to the magnitude of non-communicable diseases (NCDs) and is responsible for premature deaths globally. Objective: This study aimed to examine physical inactivity and associated factors among community dwelling adults in Abia State, Nigeria. Methods: A total of 868 community-dwelling adults (20 to 59 years) were sampled in a cross- sectional survey using multistage sampling technique. A validated questionnaire was used to collect information on sociodemographic and lifestyle characteristics. Weight and height were measured and used to calculate the body mass index (BMI). The Global Physical Activity Questionnaire (GPAQ) was used to collect data on physical activity status. Univariate and multivariate logistic regression were used to assess the relationship between physical inactivity and associated factors at p<0.05. Results: The prevalence of physical inactivity was 49.8% (48.5% in males and 51.0% in females), while combined overweight and obesity was 39.4%. In the adjusted model, physical inactivity was associated with older age (OR=0.49, 95% CI: 0.34- 0.71), increasing BMI (OR=0.67, 95% CI: 0.49- 0.91), increasing income (OR=0.65, 95% CI: 0.48- 0.89), and alcohol consumption (OR=0.67, 95% CI: 0.47- 0.97). Conclusion: The high prevalence of physical inactivity among adults underscores the need for community-based physical activity interventions to reduce the burden of NCDs among adults.